Pengaruh Belanja Modal Dan Belanja Sosial Pemerintah Terhadap Tingkat Kemiskinan Dengan Pertumbuhan Ekonomi Sebagai Variabel Intervening Di Kota Medan - Muhammad Musthofa; Tri Indah Fadhilah; Khairina Tambunan (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the influence between the interest in capital expenditure and social expenditure of the Medan City government on the poverty rate with economic growth in Medan City. This research is quantitative research. The data used is sourced from BPS (Central Statistics Agency). The analysis used in this study is multiple linear regression analysis, processed using SPSS Program Version15.0. The results of the study show that: 1). The effect of capital expenditure on the economic growth of Medan City is H a accepted and H0 rejected, that partially capital expenditure has a significant and positive effect. 2). The effect of social spending on economic growth in Meda n Cityis H a accepted and H0 rejected, that partially social spending has a significant and positive effect. 3). The effect of economic growth on the poverty rate of Medan City is H a accepted and H 0 rejected, that partially economic growth has a significant and negative effect. 4). The effect of capital expenditure on the poverty rate in Medan City is H a accepted and H0 rejected, that partially capital expenditure has a significant and positive effect. 5). The effect of social spending on the poverty rate in Medan City is H a accepted and H0 rejected, that partially social spending has a significant and negative effect. 6). The effect of capital expenditure and social expenditure on poverty rates through economic growth in Medan City has a significant effect. 7). The effect of capital expenditure and social expenditure and economic growth on the poverty rate in Medan City is then H a is accepted and H0 is rejected. With the meaning that simultaneously economic growth is able to mediate capital expenditure, social spending affects the poverty rate in Medan City.